PEMERIKSAAN ANGKA KUMAN DAN JAMUR SERTA IDENTIFIKASINYA PADA JAMU GENDONG TEMU IRENG DAN KUNYIT ASAM DI KECAMATAN GAJAHMUNGKUR SEMARANG - maulita cut nuria; yeni lutfiani; sulasmi sulasmi; sumantri sumantri (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTThe herbal tonic is a product made from natural ingredients processed in traditional ways. A traditional herb made from Temu Ireng (Curcuma aeruginosa) is a kind of herb that still consumed by relatively many Indonesian citizens for enhanching appetite and acid turmeric often consumed by female for reducing the problems when they get haid. However, bacteria and fungi might grow in this traditional herb because of contaminated water (the diluting agent) and moisture, hygiene and sanitation factors. This study, therefore, was intended to find out the quantities and the species of these bacteria and fungi growing in the herb as it is sold in Gajah Mungkur district of Semarang City. This study also intended to compare these quantities to the prevailing standard stipulated. The samples for this study were taken from 36 producers Temu Ireng and acid turmeric herb, located in Gajah Mungkur District. The medium used for growing the material in an aerobic manner was PCA (Plate Count Agar), that used for growing in an anaerobic manner were TSA (Tripticase Soya Agar) and that used for growing the fungi were PDA (Potato Dextrose Agar). For counting the bacteria, we used the method of Standard Plate Count, for identifying the bacteria we used Gram Painting and chemical tested, and for identifying the fungi we used a 100-times amplifying microscope. The analysis showed in the sample Temu Ireng and acid turmeric are the average number of bacteria at the aerobic media were 7,4 x 106 and 2,1 x 105 CFU/ml, the average number of bacteria at the anaerobic media were 4,2 x 102 and 4,3 x 102 CFU/ml, the average number of fungi were 1,5 x 102 and 1,0 x 102 CFU/ml. The aerobic bacteria found in the study were Staphylococcus aureus, Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa, the anaerobic bacteria was peptococcus, and the fungi were Penisillium, Moniliaceae, A. niger, dan Rhizopus. Nearly all samples examined in this study did not meet the conditions based on statement Indonesia Minister of Health No 661/MENKES/SK/VII/1994 because they exceeded the upper limit bacteria (104 CFU/ml) and also contain pathogenic bacterias. However, the number of fungi did not exceed the prevailing standard. Keywords: Temu Ireng Herb, Acid Turmeric Herbs, Bacteria Number and Fungi Number.